"Geographiedidaktische Forschungen" (GDF) from 1977 to 2017–A Possible Mirror of the Development and the Discourses on Geography Didactics in Germany Over the Past 40 Years? - Krautter, Yvonne; Hemmer, Michael; Schubert, Jan Christoph (Journal of Geography Education, 2017)
On the occasion of the 40th anniversary of the publication series "Geographiedidaktische Forschungen" by Hochschulverband für Geographiedidaktik (HGD) this article gives a look back at the development of the series and, at the same time, highlights on future areas of action. In addition to information on the objectives, founding contexts and formal and personal changes in the series,  the focus is on the documentation of the 67 volumes published so far, their thematic focuses and contribution formats.
Keywords: research in geography education, publication series, Hochschulverband für Geographiedidaktik